'We, the people' in Poland: democracy of 'ordinary people' in the statements of politicians and posts on social media. Issue 5 (20th October 2021) - Mocek, Stanisław
ABSTRACT : In this research constructivist grounded theory was used to explore the style and content of 300 posts on the subject of democracy on the Facebook pages of the main political parties in Poland. Analysis of the data, collected from 2016 to mid-2017, resulted in the construction of two typologies that identify distinct rhetorical and thematic types of popular political discourse. In stark contrast to previous forecasts of the ultimate triumph of liberal democracy in Eastern Europe, Polish netizens' conceptualisation of democracy is often procedural, tribal and majoritarianist. Furthermore, a comparison of such social media posts with diverse pronouncements of leading politicians reveals that popular discourse on democracy is largely generated and shaped top-down by the country's political elite.